Consequences, Motives, and Expectancies of Consumption as Predictors of Binge Drinking in University Women - Cortés-Tomás, María-Teresa; Giménez-Costa, José-Antonio; Motos-Sellés, Patricia; Sancerni-Beitia, María-Dolores (Frontiers in Psychology, 2022)
The increasing presence of women, especially university women, in risky alcohol consumption such as Binge Drinking (BD), which is associated with gender-specific biopsychosocial problems, makes it necessary to analyse the variables underlying BD in order to adjust possible interventions more in line with their reality. The motives and expectancies of this pattern of consumption, as well as the consequences derived from it, are some of the variables that are shown to have the greatest weight in the prediction of BD. In the present study we analyse, on the one hand, the performance of these variables among college women with alcohol use , and on the other hand, which of these variables allow us to classify BD. A total of 501 female university consumers of alcohol (mean age 19.02 years) were assessed. Specifically, they completed a self-report of alcohol consumption (77.1% engage in BD), the Expectancy Questionnaire (EQ), the Drinking Motives Questionnaire (DMQ-R) and the Alcohol Consumption Consequences Evaluation (ACCE). BD female students scored significantly higher on these instruments, except for compliance motives. The logistic regression analysis carried out to estimate the probability of performing BD using the social and conformity motives, the ACCE and positive expectancies correctly estimated (28= 9.149, p<0.33) 88.6% of the cases and explained 26.2% of the BD. Thus, young women with a level of consequences classified as high risk (>25 in ACCE) have a 3.55 fold increase in the probability of having BD, compared to women classified as low risk by the ACCE. On the other hand, women classified as moderate risk by the ACCE have a 4.77 fold increase in the probability of having BD. In the case of social motives and positive expectancies, their increase multiplies by 1.165 and 1.024 respectively the probability of having BD. The results of this study highlight the importance of adapting preventive measures to the consequences experienced by BD university students, especially in relation to the social motives and positive expectancies that modulate decision-making when engaging in this pattern of consumption.